(untitled) (Research, Society and Development, 2021)
Identify and analyze the relationship between the assistance of nursing professionals affected by Burnout Syndrome and Patient Safety. It is an Integrative Literature Review that systematizes the scientific evidence regarding the object of study in question, complying with the recommendations of PRISMA) and developed in six stages: 1) identification of the theme and formulation of the guiding question; 2) literature search; 3) categorization of studies; 4) evaluation of the included studies; 5) interpretation of results; 6) synthesis of knowledge. The search in the databases reached a total of 8396 studies, of which 15 were selected to compose the final sample of the review after the selection process was carried out. Therefore, the objectives were achieved, and it was established, through investigation, identification and analysis that exhausting experiences in the long-term work environment make nursing professionals sick, and the professionals affected by the SB are unable to provide quality care, thus weakening it. luck, patient safety.